2015
DOI: 10.1016/j.breast.2015.03.008
|View full text |Cite
|
Sign up to set email alerts
|

Hyperthermia and radiation therapy for locally advanced or recurrent breast cancer

Abstract: Introduction This study aims to report the outcome and toxicity of combined hyperthermia (HT) and radiation therapy (RT) in treatment of locally advanced or loco-regionally recurrent breast cancer. Patients and Methods Patients treated with HT and RT from January 1991 to December 2007 were reviewed. RT doses for previously irradiated patients were >40 Gy and for RT naïve patients >60 Gy, at 1.8–2 Gy/day. HT was planned for 2 sessions/week, immediately after RT, for a minimum of 20 minutes and for >4 sessions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 21 publications
(15 reference statements)
1
29
0
Order By: Relevance
“…This systematic review shows that for patients with locoregional recurrent breast cancer treated with RT þ HT higher temperature and/or thermal dose during HT improves CR, LC and OS [4,15,[27][28][29][30][31][32][33][35][36][37]39,40,42], while increasing the incidence of thermal toxicity [33,36,[39][40][41]48,49]. It is intriguing to see that the CR of patients who received RT alone versus patients who received RT þ low dose HT were comparable; 38.1% [6] versus 36.2% (Figure 4), respectively.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…This systematic review shows that for patients with locoregional recurrent breast cancer treated with RT þ HT higher temperature and/or thermal dose during HT improves CR, LC and OS [4,15,[27][28][29][30][31][32][33][35][36][37]39,40,42], while increasing the incidence of thermal toxicity [33,36,[39][40][41]48,49]. It is intriguing to see that the CR of patients who received RT alone versus patients who received RT þ low dose HT were comparable; 38.1% [6] versus 36.2% (Figure 4), respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Eight studies reported a significant univariate relationship between CR and thermal dose [28][29][30][31] or temperature [32,33,39,42] (Figure 3 and Table 1). Four studies [29,34,35,39] reported a trend (p < .1) between temperature and CR, while two studies did not find any relationship between CR and thermal dose parameters [43,44].…”
Section: Complete Responsementioning
confidence: 99%
See 3 more Smart Citations